New insights of the role of β-NGF in the ovulation mechanism of induced ovulating species. Issue 5 (May 2019) - Ratto, Marcelo H; Berland, Marco; Silva, Mauricio E; Adams, Gregg P
Abstract : The type of stimuli triggering GnRH secretion has been used to classify mammalian species into two categories: spontaneous or induced ovulators. In the former, ovarian steroids produced by a mature follicle elicit the release of GnRH from the hypothalamus, but in the latter, GnRH secretion requires coital stimulation. However, the mechanism responsible for eliciting the preovulatory LH surge in induced ovulators is still not well understood and seems to vary among species. The main goal of this review is to offer new information regarding the mechanism that regulates coitus-induced ovulation. Analysis of several studies documenting the discovery of β-NGF in seminal plasma and its role in the control of ovulation in the llama and rabbit will be described. We also propose a working hypothesis regarding the sites of action of β-NGF in the llama hypothalamus. Finally, we described the presence of β-NGF in the semen of species categorized as spontaneous ovulators, mainly cattle, and its potential role in ovarian function. The discovery of this seminal molecule and its ovulatory effect in induced ovulators challenges previous concepts about the neuroendocrinology of reflex ovulation and has provided a new opportunity to examine the mechanism(s) involved in the cascade of events leading to ovulation. The presence of the factor in the semen of induced as well as spontaneous ovulators highlights the importance of understanding its signaling pathways and mechanism of action and may have broad implications in mammalian fertility.